2021
DOI: 10.1001/jamanetworkopen.2021.16839
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variants Associated With Intraparenchymal Hemorrhage Progression After Traumatic Brain Injury

Abstract: IMPORTANCE Intracerebral hemorrhage progression is associated with unfavorable outcome after traumatic brain injury (TBI). No effective treatments are currently available. This secondary injury process reflects an extreme form of vasogenic edema and blood-brain barrier breakdown. The sulfonylurea receptor 1-transient receptor potential melastatin 4 (SUR1-TRPM4) cation channel is a key underlying mechanism. A phase 2 trial of SUR1-TRPM4 inhibition in contusional TBI is ongoing, and a phase 3 trial is being desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 56 publications
0
25
0
Order By: Relevance
“…In a series of targeted investigations into the impact of ABCC8 and TRPM4 genetic variability on secondary injury after TBI in a single-center cohort of 385–485 patients with severe TBI, they identified several regionally clustered polymorphisms in both genes that were consistently associated with measures of intracranial hypertension, radiographic edema, and hemorrhage progression. The effect sizes were large, and findings were biologically consistent [ 135 , 136 , 137 , 144 , 145 ]. Although only approximately 1% of polymorphisms in ABCC8 (and TRPM4 ) are linked with brain-specific mRNA levels (i.e., brain-specific expression quantitative trait loci; eQTL), all the single nucleotide polymorphisms identified as significantly associated with hemorrhage progression after TBI were eQTLs with biologically concordant effects.…”
Section: Sur1-trpm4 Expression and Inhibition In Cns Injurymentioning
confidence: 89%
See 1 more Smart Citation
“…In a series of targeted investigations into the impact of ABCC8 and TRPM4 genetic variability on secondary injury after TBI in a single-center cohort of 385–485 patients with severe TBI, they identified several regionally clustered polymorphisms in both genes that were consistently associated with measures of intracranial hypertension, radiographic edema, and hemorrhage progression. The effect sizes were large, and findings were biologically consistent [ 135 , 136 , 137 , 144 , 145 ]. Although only approximately 1% of polymorphisms in ABCC8 (and TRPM4 ) are linked with brain-specific mRNA levels (i.e., brain-specific expression quantitative trait loci; eQTL), all the single nucleotide polymorphisms identified as significantly associated with hemorrhage progression after TBI were eQTLs with biologically concordant effects.…”
Section: Sur1-trpm4 Expression and Inhibition In Cns Injurymentioning
confidence: 89%
“…Although only approximately 1% of polymorphisms in ABCC8 (and TRPM4 ) are linked with brain-specific mRNA levels (i.e., brain-specific expression quantitative trait loci; eQTL), all the single nucleotide polymorphisms identified as significantly associated with hemorrhage progression after TBI were eQTLs with biologically concordant effects. For example, ABCC8 eQTLs associated with increased brain-specific ABCC8 mRNA levels were also associated with increased odds of hemorrhage progression [ 145 ]. Regulatory annotations of these regions further revealed promotor and enhancer marks, as well as active brain-tissue transcription start sites.…”
Section: Sur1-trpm4 Expression and Inhibition In Cns Injurymentioning
confidence: 99%
“…There is potential for clinical relevance here, given that recent studies of septic patients have demonstrated both serum biomarker evidence of axonal injury, notably increases in neurofilament light, along with MRI evidence [ 46 , 47 ]. Finally, recent studies in TBI have suggested significant genetic variability in Abcc8 –TRPM4 between patients that is strongly associated with its role in mediating secondary damage [ 48 , 49 ]. This suggests the possibility of precision-directed therapy, thereby warranting further investigation into the genetic underpinning of this pathway in patients with septic encephalopathy [ 21 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the CC genotype of rs1799858 and rs141294036 correlates only with moderate and high risk of IS. In addition to being related to the occurrence risk, a recent study further showed that the KATP variants (e.g., rs2237982, rs2283261, rs3819521, and rs8192695) are also linked to the progression of vascular events, and are involved in abnormal transcription in the target-tissue and promoter/enhancer markers ( 41 ). Compared to the heritabilityof rs141294036 for new-onset stroke risk (0.44%, Supplementary Table 6 ), the heritability of the loci for new-onset/recurrent ACS risk (1.34%, Supplementary Table 5 ) are much higher.…”
Section: Discussionmentioning
confidence: 99%